Confocal Endomicroscopy Identifies Loss of Local Barrier Function in the Duodenum of Patients with Crohn's Disease and Ulcerative Colitis. Issue 5 (31st March 2014) - Lim, Lee G.; Neumann, Janina; Hansen, Torsten; Goetz, Martin; Hoffman, Arthur; Neurath, Markus F.; Galle, Peter R.; Chan, Yiong H.; Kiesslich, Ralf; Watson, Alastair J.
Abstract : Background: Increased cell shedding with gap formation and local barrier dysfunction can be identified endomicroscopically in the terminal ileum of patients with inflammatory bowel disease. We aim to evaluate whether these changes are also present in the duodenum of patients with inflammatory bowel disease. Methods: Fifteen patients with Crohn's disease (CD), 10 patients with ulcerative colitis (UC), and 10 controls underwent fluorescein-aided confocal laser endomicroscopy (CLE). CLE was performed on macroscopically normal antral and duodenal (D1, D2, D3, D4) mucosa. Representative CLE images were prospectively analyzed. Images were scored for the number of epithelial gaps, cell shedding, and the degree of fluorescein leakage into the intestinal lumen. Results: Both CD and UC patients had significantly more epithelial gaps, epithelial cell shedding, and leakage of fluorescein into the duodenal lumen than controls. The degree of cell shedding and epithelial gap formation was similar in CD and UC patients. In all cases, macroscopic endoscopic appearances of the duodenum were normal, and conventional histological analysis showed a mild nonspecific duodenitis in 7 of 15 patients with CD. Patients with UC had a histologically normal duodenum. Gap formation, cell shedding, and fluorescein leakage was similar in CD with active compared with inactive disease, except for D2 shedding. Conclusions: CLE can detect epithelial damage and barrier loss in the duodenum of CD and UC patients that is not apparent on conventional endoscopy or histology.